Ability to Write Anecdote Text by Using Caricature Media on 10th Grade Students of SMA Swasta Swakarya Binjai - M. Natsir; Bahagia Saragih; Rafika Dewi (RIRAI Publisher, 2021)
This study aims to determine the effect of caricature media on the ability to write anecdote text on 10th Grade Students of SMA Swasta Swakarya Binjai School Year 2018/2019. The population of this research is 125 students. Of the 125 students, a sample of 35 students are selected who were taken using a random sample. The method used in this study is a quasih experimental two group post-test design. The instrument used to collect data is the description test. Hypothesis testing is done using the